Does Branched-Chain Amino Acids Supplementation Modulate Skeletal Muscle Remodeling through Inflammation Modulation? Possible Mechanisms of Action - Humberto Nicastro; Claudia Ribeiro da Luz; Daniela Fojo Seixas Chaves; Luiz Roberto Grassmann Bechara; Vanessa Azevedo Voltarelli; Marcelo Macedo Rogero; Antonio Herbert Lancha (Journal of Nutrition and Metabolism)
Skeletal muscle protein turnover is modulated by intracellular signaling pathways involved in protein synthesis, degradation, and inflammation. The proinflammatory status of muscle cells, observed in pathological conditions such as cancer, aging, and sepsis, can directly modulate protein translation initiation and muscle proteolysis, contributing to negative protein turnover. In this context, branched-chain amino acids (BCAAs), especially leucine, have been described as a strong nutritional stimulus able to enhance protein translation initiation and attenuate proteolysis. Furthermore, under inflammatory conditions, BCAA can be transaminated to glutamate in order to increase glutamine synthesis, which is a substrate highly consumed by inflammatory cells such as macrophages. The present paper describes the role of inflammation on muscle remodeling and the possible metabolic and cellular effects of BCAA supplementation in the modulation of inflammatory status of skeletal muscle and the consequences on protein synthesis and degradation.